Knowledge of Budgets and Board Performance in County Financial Oversight: Professional Commitment as Moderating - Hardianto; Adi Rahmat; Adolf Bastian (Yayasan Education Al Aqsho Modern, 2023)
This study aims to explain and analyze the effect of budget knowledge on the performance of the Riau Provincial DPRD in regional financial supervision with professional commitment as moderating. This study uses this research using quantitative methods and the PLS Structural equational modeling (SEM) statistical test will be used for verifiable analysis. The study was conducted in the Regional People's Representative Council of Riau Province with a total of 65 respondents. The results showed that budget knowledge positively affects the performance of regional financial supervision by the Riau Provincial DPRD. This means that the better the budget knowledge possessed by the board members, the higher the level of performance of regional financial supervision by the Riau Provincial DPRD. Professional commitment has a positive influence on the performance of regional financial supervision by the Riau Provincial Legislature. This means that the higher the level of professional commitment owned by each board member, the higher the level of performance of regional financial supervision by the Riau Provincial DPRD. Professional commitment as a Moderating Variable does not affect the variable performance of regional financial supervision by the Riau Provincial DPRD. This means that the professional commitment variable as moderating will weaken the relationship of the budget knowledge variable to the regional financial supervision performance variable by the Riau Provincial DPRD, because indeed the performance of regional financial supervision by the Riau Provincial DPRD will not run well even though it is supported by the budget knowledge possessed by each board member if the board members cannot distinguish or even sort between their professional commitments to the institutions of the Riau Provincial Legislature with their professional commitment to the organization of the political party from which they belong.